Nilai Ekonomi Pendayagunaan Konsumtif Hijauan Makanan Ternak yang Dimanfaatkan oleh Masyarakat dari Kawasan Hutan - Fahriza Riza Luth (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
ABSTRACTCattle food greenery is an important factor in supporting ruminant farming to improve optimally with good result besides breeding factor and procedures. Ruminant farming needs greenery feeding at least 10% of its weight to fill up its energy needs. A good quality feeding must be provided continually to support the ruminant farming. People in villages use farming areas, plantations, and vacant areas along the streets as plant production area for their livestock, and people living near the forests use forest area as greenery source for their cattle. However, people recently have little awareness to preserve the forest due to their lack of knowledge to value the advantages of the forest they benefit from every day. This circumstances frequently lead to pressure towards the forest. This research is aimed to find out the amount of cattle food greenery in every family unit monthly, to know the economy value of cattle food greenery which is earned by the people from the forest area, and to inform people to raise ther knowledge and awareness towards the importance of forest use and its preservation. This research used survey method to obtain data in current condition by involving 140 respondents. The result shows that there are 8.650 sacks (50 kg each) of cattle food greenery which are earned by each family unit from the forest, with 62 sacks approximately. The total economy value of cattle food greenery is Rp. 126.600.000 monthly with the average number as much as Rp. 904.285,71 per family unit.